Action COST 621 »Groundwater management of coastal karstic aquifers« - Metka Petrič; Janja Kogovšek; Janko Urbanc (Geologija, 2002)
COST 621 »Groundwater management of coastal karstic aquifers” is an international project in the frame of the European Union in which 12 European countries, including Slovenia, took an active part in the years 1997-2002. The main objective of the Action is to increase the knowledge necessary to establish criteria for improving groundwaterresource utilisation in karstic coastal aquifers and for recovering groundwater resource in aquifers over-exploited and salinised due to sea water intrusion. Based on gathered results “Guidelines for the groundwater management of coastal karstic aquifers” were compiled and will be published as a special booklet. In this way the dissemination of the results will be provided.